Dairy powders and concentrated products - Tamime, A. Y. (Society of Dairy Technology series., 2009)
The latest addition to the successful Society of Dairy Technology series, this book details the manufacturing methods, scientific aspects and properties of milk powders (full-fat, skimmed and high protein powders made from milk retentates); whey powders; lactose; caseinates; sweetened condensed milk and evaporated milk. The book also examines the cleaning and disinfection of equipment, together with potential hazards (such as explosion and fire) that may occur during the manufacture of dairy powders. International legislation governing standards of these products for trading purposes is covere.